Service Quality dan Marketing Mic dalam Menunjang Keberhasilan UMKM Makanan di Kecamatan Coblong, Kota Bandung - Annisa Azzahra (Pusat Riset dan Inovasi Nasional, 2024)
The growth of MSMEs in Indonesia, particularly in the culinary sector, holds substantial potential for bolstering the national economy, with Coblong District in Bandung City emerging as a rapidly developing hub; however, despite the fierce competition, the success of culinary MSMEs in this area is influenced not only by product quality but also by factors such as service quality and the marketing mix, prompting this study to investigate their contribution to the success of culinary MSMEs in Coblong District, using a quantitative approach where data from 36 MSMEs were collected via questionnaires, and although the results of multiple linear regression analysis reveal that neither service quality nor the marketing mix have a significant impact on the success of these MSMEs, both factors still play an essential role in supporting customer satisfaction and achieving business goals.